A DNA methylation classifier of cervical precancer based on human papillomavirus and human genes. Issue 6 (5th March 2014) - Brentnall, Adam R.; Vasiljević, Nataša; Scibior‐Bentkowska, Dorota; Cadman, Louise; Austin, Janet; Szarewski, Anne; Cuzick, Jack; Lorincz, Attila T.
<x xml:space="preserve">Abstract</x> Testing for high‐risk (hr) types of human papillomavirus (HPV) is highly sensitive as a screening test of high‐grade cervical intraepithelial neoplastic (CIN2/3) disease, the precursor of cervical cancer. However, it has a relatively low specificity. Our objective was to develop a prediction rule with a higher specificity, using combinations of human and HPV DNA methylation. Exfoliated cervical specimens from colposcopy‐referral cohorts in London were analyzed for DNA methylation levels by pyrosequencing in the L1 and L2 regions of HPV16, HPV18, HPV31 and human genes EPB41L3, DPYS and MAL. Samples from 1, 493 hrHPV‐positive women were assessed and of these 556 were found to have CIN2/3 at biopsy; 556 tested positive for HPV16 (323 CIN2/3), 201 for HPV18 (73 CIN2/3) and 202 for HPV31 (98 CIN2/3). The prediction rule included EPB41L3 and HPV and had area under curve 0.80 (95% CI 0.78–0.82). For 90% sensitivity, specificity was 36% (33–40) and positive predictive value (PPV) was 46% (43–48). By HPV type, 90% sensitivity corresponded to the following specificities and PPV, respectively: HPV16, 38% (32–45) and 67% (63–71); HPV18, 53% (45–62) and 52% (45–59); HPV31, 39% (31–49) and 58% (51–65); HPV16, 18 or 31, 44% (40–49) and 62% (59–65) and other hrHPV 17% (14–21) and 21% (18–24). We conclude that a methylation assay in hrHPV‐positive women might improve PPV with minimal sensitivity loss.